Wenzhouxiangella Strain AB-CW3, a Proteolytic Bacterium From Hypersaline Soda Lakes That Preys on Cells of Gram-Positive Bacteria - Sorokin, Dimitry Y.; Mosier, Damon; Zorz, Jackie K.; Dong, Xiaoli; Strous, Marc (Frontiers in Microbiology, 2020)
A new haloalkaliphilic species of Wenzhouxiangella, strain AB-CW3, was isolated from a system of hypersaline alkaline soda lakes in the Kulunda Steppe using cells of Staphylococcus aureus as growth substrate. AB-CW3’s complete, circular genome was assembled from combined nanopore and Illumina sequencing and its proteome was determined for three different experimental conditions. AB-CW3 is an aerobic gammaproteobacterium feeding mainly on proteins and peptides. Unique among Wenzhouxiangella, it uses a flagellum for motility, fimbria for cell attachment and is capable of complete denitrification. AB-CW3 can use proteins derived from living or dead cells of Staphylococcus and other Gram-positive bacteria as the carbon and energy source. It encodes and expresses production of a novel Lantibiotic, a class of antimicrobial peptides which have so far only been found to be produced by Gram-positive bacteria. AB-CW3 likely excretes this peptide via a type I secretion system encoded upstream of the genes for production of the Lanthipeptide. Comparison of AB-CW3’s genome to eighteen other Wenzhouxiangella genomes from marine, hypersaline and soda lake habitats indicated one or two transitions from marine to soda lake environments followed by a transition of W. marina back to the oceans. Only nineteen genes appear to set haloalkaliphilic Wenzhouxiangella apart from their neutrophilic relatives. As strain AB-CW3 is only distantly related to other members of the genus, we propose to provisionally name it Candidatus “Wenzhouxiangella alkaliphila”.